A Novel Fusion Approach by Non-Sub Sampled Contourlet Transform (International Journal of Engineering and Computer Science, 2015)
In This project we analyzes the characteristics of the non-sub sampled counterlet Transform and put forward an image fusion algorithm based on Wavelet Transform and the Second Generation Curvelet Transform method. We would take the selection principles that all about low and high frequency coefficients according to different frequency domain after Wavelet and the Second Generation Curvelet Transform. We first measure the STD (stranded deviation) of low frequency components and high frequency components. The window property and local characteristics of pixels were analyzed in this method. Totally, the proposed algorithm in this paper was appalling to the experiments of multi focal image fusion and also complementary image fusion. In accordance with the final results the proposed method hold useful information with other method